Economic effectivity of fairs – KAVA Model testing on agricultural exhibitions - Kárpáti , László; Varga, Levente (Applied Studies in Agribusiness and Commerce, 2009)
This paper discusses the first experiences with the newly-developed KAVA-model. This model works on cash basis and evaluates cash inflow, outflow and Net Cash-Flow (NCF) in connection with four different interest groups connected to the given exhibition. The model was tested on four different exhibitions: Farmerexpo (Debrecen, Hungary) in 2005 and 2006, OMÉK (Budapest, Hungary) from 2005 and PolagraFarm (Poznan, Poland) 2006.The different fairs can be compared by their relative „economic values” that makes the auditing more reliable.